US trade aid payments and the WTO - Glauber, Joseph W. (Agricultural and Applied Economics Association, 2021)
The trade wars initiated by the Trump Administration in 2018 had an adverse effect on US agriculture. Countertariffs imposed by US trading partners had significant effects on US commodity exports, particularly soybeans, and lowered crop and livestock receipts. To shore up political support from farmers, the Trump administration authorized an estimated total of $28 billion to farmers and ranchers in compensation for export losses. While those payments will help the sector in the short term, the aid payments could well prolong problems for the sector beyond 2020 by exacerbating trade tensions and precipitating future WTO disputes.